Oral cannabidiol (CBD) as add-on to paracetamol for painful chronic osteoarthritis of the knee: a randomized, double-blind, placebo-controlled clinical trialResearch in context - Sibylle Pramhas; Teresa Thalhammer; Sebastian Terner; Daniel Pickelsberger; Andreas Gleiss; Sabine Sator; Hans G. Kress (Elsevier, 2023)
Summary: Background: Painful knee osteoarthritis (KOA) is common, pharmacological treatment, however, is often hampered by limited tolerability. Cannabidiol, which preclinically showed anti-inflammatory, analgesic activity, could supplement established analgesics, but robust clinical trials are lacking. The aim of our study was to investigate the effects of oral high-dose CBD administered over 8 weeks on pain, function and patient global assessment as an add-on to continued paracetamol in chronic symptomatic KOA. Methods: Prospective, randomized, placebo-controlled, double-blind, parallel-group study. Single center, Outpatient Clinic, Department of Special Anaesthesia and Pain Therapy at Medical University of Vienna, Austria. Eligibility criteria included: age: 18-98 years; painful KOA; score ≥5 on the pain subscale of the Western Ontario and McMasters Universities Osteoarthritis (WOMAC) Index; KOA confirmed by imaging. Participants were on continued dosage of paracetamol 3 g/d and randomly assigned by web-based software 1:1 to oral cannabidiol 600 mg/d (n = 43) or placebo (n = 43). Study period: 8 weeks. Primary outcome: Change in WOMAC pain subscale scores (0 = no pain, 10 = worst possible pain) from baseline to week 8 of treatment. Trial Registration: ClinicalTrials.gov Identifier: NCT04607603. Trial is completed. Findings: The trial was conducted from October 1, 2020 to March 29, 2022. 159 patients screened, 86 randomized. Among 86 participants (mean age, 62.8 [SD 20.3] years; 60 females [69.8%]), 58 (67.4%) completed the trial. Mean baseline WOMAC pain subscale was 6.0 ± 1.1. Analysis: Intention-to-treat principal. Mean reduction in WOMAC pain subscale was 2.5 (95% CI: 1.8-3.3) in the cannabidiol group and 2.4 (95% CI: 1.7-3.2) in the placebo group with no significant group difference (p = 0.80). Adverse events were significantly more frequent with cannabidiol (cannabidiol: 135 [56%]; placebo: 105 [44%]) (p = 0.008). Rise above baseline of liver aminotransferases and gamma-glutamyltransferase was significantly more common in the cannabidiol (n = 15) than the placebo group (n = 5) (p = 0.02). Interpretation: In KOA patients, oral high-dose add-on cannabidiol had no additional analgesic effect compared to adding placebo to continued paracetamol. Our results do not support the use of cannabidiol as an analgesic supplement in KOA. Funding: Trigal Pharma GmbH.